Desenvolvimento e caracterização de compósitos de PET com partículas metálicas com atividade antimicrobiana - Guerra, Marcos Antônio (2015)
The aim of this study was to develop composites with copper microparticles in spherical form (MPCu-esf) and flake form (MPCu-flake), with copper nanoparticles (NPCu) and silver nanoparticles (NPAg+Si) in different concentrations in the poly(ethylene terephthalate)–PET matrix. Filaments were produced from these composites, whose the antimicrobial activity in vitro was characterized and compared between the composites. The standard method was according to AATCC-100 for assessment of the bactericidal effect metallic particles in bacteria S. aureus and Klebsiella pneumoniae. A time of 24 hours for incubation was used. The mechanical properties such as tenacity and elongation, thermal and optical properties were also evaluated for the purpose of ensuring that these properties for fiber production, were not affected so as to prevent fiber production on an industrial scale. The results confirm the satisfactory antimicrobial characteristics to the nanocomposites produced from the MPCu-spherical and NPCu, both the minimum concentration of 0.022% m/m and the NPAg-Si at minimum concentration of 0.045% m/m. Regarding to mechanical properties, there was little decrease in tenacity and elongation increase for all nanocomposites. Regarding to mechanical properties, there was little decrease in tenacity and elongation increase for all composites. With respect to thermal properties, there was reduction in the crystallization and crystalline melting temperature for the composites with increasing concentration of the metal particles. For to optical properties, it was observed that the color a * (green - red) increased toward the red color and the b * color (blue - yellow) increased toward yellow color with increasing concentration of the particles and the color L* (brightness), reduced with increasing particle concentration. Information obtained from this study will be relevant for the production of fabrics and nonwovens for medical application, hospital, hygiene and clothing. In addition to these applications, as PET is also used for manufacturing food packaging in the form of bottles and films, the composites can be exploited for greater shelf-life of food.